If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3lx + -2l + 1 = 1 Reorder the terms: 1 + -2l + 3lx = 1 Add '-1' to each side of the equation. 1 + -2l + -1 + 3lx = 1 + -1 Reorder the terms: 1 + -1 + -2l + 3lx = 1 + -1 Combine like terms: 1 + -1 = 0 0 + -2l + 3lx = 1 + -1 -2l + 3lx = 1 + -1 Combine like terms: 1 + -1 = 0 -2l + 3lx = 0 Solving -2l + 3lx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'l'. l(-2 + 3x) = 0Subproblem 1
Set the factor 'l' equal to zero and attempt to solve: Simplifying l = 0 Solving l = 0 Move all terms containing l to the left, all other terms to the right. Simplifying l = 0Subproblem 2
Set the factor '(-2 + 3x)' equal to zero and attempt to solve: Simplifying -2 + 3x = 0 Solving -2 + 3x = 0 Move all terms containing l to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 0 + 2 3x = 0 + 2 Combine like terms: 0 + 2 = 2 3x = 2 Add '-3x' to each side of the equation. 3x + -3x = 2 + -3x Combine like terms: 3x + -3x = 0 0 = 2 + -3x Simplifying 0 = 2 + -3x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
l = {0}
| -9d=18 | | 14y-9=15 | | -3n+-14=-3n+-30 | | -2r+-1=-11 | | (6+v)(5v+9)=0 | | -13x+9y=-6 | | 8m-3-9m-m=5-12 | | N+n-6=30 | | 5x-18+4x+7= | | 12r^3-5r^2-2r=0 | | -52=-4s | | 14-(6+m)=22 | | 2p-p-1=17 | | 2d+-4=-4+3d | | 8x-11+2x+6=180 | | 6x+20=50 | | 10=2(p-7)+6 | | 7m-(3+m)+8-4m=9 | | factoringx^2+2x=0 | | 8m+5(1-m)-4m=-6 | | 4.6=a-3 | | 10r=20 | | 3m-5-4m-m=7-8 | | 13a+-17a+-4a=8 | | m-(8-m)=32 | | 8x-11+2x+6+5x=180 | | 8x+-7=2(2x+7)+-5 | | 15=3(w-11) | | -7m-(m+4)-3(7-m)=0 | | 0=x^2+8x-32 | | 0.40m-7=16 | | 2(q+4)+-7=-1 |